Optimization of Milk Pasteurization Process Using PID Control System - Firdausi, Hasanur Mohammad; Cahyono, Yusuf Fani Dwi; Rahardi, Gamma Aditya; Ghozali, Moch; Muldayani, Wahyu; Herdiyanto, Dedy Wahyu (Jurnal Arus Elektro Indonesia, 2025)
Livestock products that experience an increase in production every year are dairy products. Based on research data on national milk production in 2020, the amount of dairy products produced increased to 947,685.36 tons. Animal protein needed by the body to grow and develop and to maintain health is the source of milk. The dairy processing industry relies on fresh cow's milk. Milk needs to be further processed to extend its shelf life because milk is easily spoiled or damaged and has a relatively short shelf life as a food of animal origin. Pasteurization is a process that can be done. One effort to extend the shelf life of milk is by pasteurizing milk. The pasteurization process is carried out by heating milk at a temperature of LTLT 62°C-66°C for 30 minutes or HTST temperature of 72°C -75°C for 15 seconds. This study uses the LTLT method with a temperature of 63°C to maintain the temperature using the 2nd 2nd-orderer Nichols PID control. To apply the system, several components are used, namely, Arduino nano as a microcontroller, DS18B20 sensor as a milk temperature reader, as well as a feedback system from PID control, servo to regulate the valve used to regulate the intensity of the stove flame, and the servo, rotates according to the PID value received, MQ-02 sensor to maintain safety against LPG gas leaks. There is a 12C LCD to provide visual information on the temperature and ADC values from the MQ-02 sensor, and there is a buzzer as an indicator of the system. The buzzer will be ON when the pasteurization process time is complete and when a gas leak occurs. Then, there is a TCS3200 sensor that compares the colour of the milk.